POST-COVID-19 PANDEMIC STUDENT MUKHLIS PERSONALITY CHARACTERISTICS - Fadilah, Risydah; Sari, Ditya Indria; Parinduri, Sari Atika (Psikis : Jurnal Psikologi Islami, 2023)
This research was conducted with the aim of knowing the personality characteristics of mukhlis students after the Covid-19 pandemic. The method used in this study is descriptive method with a total sampling technique of 365 students. Based on the results of statistical calculations obtained, an overview of Mukhlis' personality characteristics was obtained for students of the Faculty of Psychology Class of 2021 UMA who had low achievements in Semester 2 of 95% and based on several aspects, namely first, the Al-Khaathir aspect (86.7%), the 'Azam ( 90%), Niyat aspect (66.7%) and Af'al aspect (93.3%). Thus it can be concluded that the Af'al aspect is more dominant in students than the Niyat aspect so that student achievement tends to decrease